Body Dissatisfaction dan Pengetahuan Gizi dengan Perilaku Makan pada Mahasiswa Kesehatan - Aslan Saputra Ui; Vivien Novarina A. Kasim; Bergita Dumar (Journal of Telenursing (JOTING), 2025)
This study aims to investigate the relationship between body dissatisfaction, nutritional knowledge, and eating behavior among health students at Gorontalo State University—a cross-sectional study using stratified random sampling that involved 91 health students in their third and fifth semesters. The results showed a significant relationship between body dissatisfaction and eating behavior (p-value = 0.000) and between nutritional knowledge and eating behavior (p-value = 0.000). In conclusion, a significant relationship exists between body dissatisfaction and eating behavior, as well as between nutritional knowledge and eating behavior, among health students.   Keywords: Body Dissatisfaction, Eating Disorders, Healthy Students, Nutrition Knowledge, Eating Behavior